Swarna Makshika Bhasma preparation using an alternative heating method to traditional Varaha Puta - Pathiraja, P.M.Y.S.; Ranatunga, Y.M.M.K.; Herapathdeniya, S.K.M.K.; Gunawardena, S.H.P. (Journal of Ayurveda and Integrative Medicine, Elsevier, 2019)
Background: Metals, minerals and gemstones are used to prepare drugs in combination with various herbal materials in ayurvedic treatments. During the process of preparation, metals, minerals or gemstones are converted into special form known as bhasma by series of pharmaceutical processes; shodhana, bhavana and marana. Puta is the amount of heat required to produce specific bhasma in a cycle of treatment in the process of marana. Traditionally, heat is produced by burning cow dung cakes and the amount of heat to be provided is described in terms of cow dung cakes (fuel) burnt. Objectives: The present study was aimed to obtain the temperature profile of the traditional Varaha Puta and to establish a complementary temperature profile in a muffle furnace. Materials and methods: The temperature profile of Varaha puta was determined using dried cow dung cakes (which were prepared using cow dung and paddy husk) with an average calorific value of 15.44 MJ/ kg as the fuel. Then temperature profile of traditional Varaha Puta was mapped with an electric muffle furnace and Swarna Makshika (Chalcopyrite) bhasma was prepared using both traditional method and in electric muffle furnace. Results: Bhasma prepared using both Varaha Puta and muffle furnace have shown similar properties according to classical tests of Ayurveda and laboratory techniques. Conclusion: The results show the possibility of using a muffle furnace to prepare Swarna Makshika bhasma instead of using traditional Varaha Puta.
Keywords: Bhasma; Chalcopyrite; Muffle furnace; Swarna Makshika; Varaha Puta